2021
DOI: 10.1111/apt.16467
|View full text |Cite
|
Sign up to set email alerts
|

A survey of gastroenterologists in the United States on the use of central neuromodulators for treating irritable bowel syndrome

Abstract: Summary Background Central neuromodulators are an effective treatment for irritable bowel syndrome (IBS) but may be used less frequently than other therapies. Aims To survey gastroenterologists in the United States (US) about their use of neuromodulators in patients with IBS. Methods A 23‐question survey was distributed to gastroenterologists in the United States. Comparisons in prescribing practices were conducted between (a) gastroenterologists who were “high prescribers” versus “low prescribers” of neuromod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…Perceived and internalized stigma can adversely affect patient outcomes 6,7 . A recent survey found that 28% of practicing gastroenterologists cited a lack of competence as a barrier to prescribing neuromodulators with another study finding than less than a quarter of gastroenterologists wrote more than 10 neuromodulator prescriptions to patients annually, despite ample evidence supporting their efficacy across a variety of DGBI conditions 8,9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived and internalized stigma can adversely affect patient outcomes 6,7 . A recent survey found that 28% of practicing gastroenterologists cited a lack of competence as a barrier to prescribing neuromodulators with another study finding than less than a quarter of gastroenterologists wrote more than 10 neuromodulator prescriptions to patients annually, despite ample evidence supporting their efficacy across a variety of DGBI conditions 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…6,7 A recent survey found that 28% of practicing gastroenterologists cited a lack of competence as a barrier to prescribing neuromodulators with another study finding than less than a quarter of gastroenterologists wrote more than 10 neuromodulator prescriptions to patients annually, despite ample evidence supporting their efficacy across a variety of DGBI conditions. 8,9 Gastroenterology fellowship is the formative period to develop competence as measured by knowledge milestones and to learn how to cultivate a therapeutic patient-physician relationship prior to entering independent practice. Both components are essential in improving satisfaction and health outcomes in patients with DGBI.…”
mentioning
confidence: 99%
“…Neuromodulators could attenuate visceral nociception and exert profound effects on peripheral nervous system (e.g., GI tract), and has been proven to be effective in the treatment of rFD ( 6 ). However, concerns about side effects and ADS were the most common barriers to neuromodulator use ( 10 , 13 ). Gastroenterologists are concerned about ADS and side effects of LC therapy and the insufficiency of efficacy of SC therapy in rFD.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing use of neuromodulators in DGBI, side effects associated with neuromodulators have emerged, which are reported to be the most common barriers to neuromodulator use ( 10 ). Besides, currently used neuromodulators are mainly slow-acting agents requiring at least 6–8 weeks for their actions, which might lead to stigma attributed to antidepressant and treatment non-adherence ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…The interest in the therapy with neuromodulators in IBS is reflected by the emergence of a new subspeciality called psychogastroenterology [26,27]. It is also reflected in the prescription practice of gastroenterologists [28]. Therefore, the aim of this review is to present an update on the use of neuromodulators in IBS.…”
Section: Introductionmentioning
confidence: 99%